Penguatan Pendidikan Karakter dan Budi Pekerti melalui Metode Story Telling Bagi Guru Pondok Darunnadwah Cikarang - Bekasi - Sigit Widiyarto; Muthia Mubasyira; Leni Tiwinyanti; Lidya Natalia Sartono; Siti Alifah; Adhis Pamungkas (Jurnal Pengabdian UntukMu NegeRI, 2020)
The Strengthening Character Education and Character through Story Telling Method with Darunnadwah Islamic Boarding School partners located at Jln. Gatot Subroto No. 55, Karangasih, North Cikarang, Bekasi, West Java is a community service program with the aim of strengthening the character education and character of students in partner locations due to the lack of understanding of the use of story telling methods in teaching and learning activities in schools. The method used is the lecture and discussion method. Pondok teachers are provided with structured material and the provision of several videos containing examples of story telling. This gives a positive influence in the form of new knowledge and skills, storytelling skills that are useful in teaching in the classroom. The results of this activity are, the enthusiasm or learning motivation of trainees should be appreciated and the teachers already have basic knowledge in applying story telling methods in strengthening character education and students' character and some techniques in reading stories in English. Keywords: Story Telling Method, Character Education, Character,